(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article reports on a study of the effectiveness of indirect correction of written error or indirect written corrective feedback in the promotion of the accurate use of subject-verb agreement in the third person singular among students with an elementary level of linguistic competence who learn English as a foreign language at the school level. The sample consisted of 39 8th grade students at a private school in the Biobío region, Chile, who were given a pre-test, an immediate post-test and a delayed post-test. The results show that the correction technique represents an effective tool for the improvement of the grammatically accurate use of subject-verb agreement even when students have a basic level of competence in the foreign language.